2012
DOI: 10.3892/etm.2012.555
|View full text |Cite
|
Sign up to set email alerts
|

Nimotuzumab prolongs survival in patients with malignant gliomas: A phase I/II clinical study of concomitant radiochemotherapy with or without nimotuzumab

Abstract: Abstract. The present study aimed to determine whether nimotuzumab enhances the effect of radiochemotherapy in malignant gliomas. Patients (n=41) with malignant gliomas were divided into 20 cases (treatment group) in which nimotuzumab plus radiochemotherapy were offered and 21 cases (control group) in which placebo and radiochemotherapy were administered to the patients. The response to treatment was evaluated according to the Response Evaluation Criteria in Solid Tumors, the Kaplan-Meier method was used to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Indeed, no CT regimen has been proven to be effective for LGBSG patients. Only few cases were reported to have a good response to CT (14,27,28). In addition, the Kaplan-Meier curves plotted both in all patients (n = 305) and non-GTR group (n = 125) supported that adjuvant therapy provided no clinical benefits.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, no CT regimen has been proven to be effective for LGBSG patients. Only few cases were reported to have a good response to CT (14,27,28). In addition, the Kaplan-Meier curves plotted both in all patients (n = 305) and non-GTR group (n = 125) supported that adjuvant therapy provided no clinical benefits.…”
Section: Discussionmentioning
confidence: 89%
“…A Phase I/II trial evaluated whether nimotuzumab enhanced the effect of radiochemotherapy in HGG (Table 1). 40 A total of 41 patients were randomized to receive 6 weekly infusions of nimotuzumab (200 mg), or placebo in addition to radiotherapy (46–66 Gy) and a temozolomide based regime. Temozolomide was administered daily (75 mg/m2) during radiation therapy.…”
Section: Clinical Experience Of Nimotuzumab In Combination With Radiomentioning
confidence: 99%
“…In our patient after treatment of TMZ (three cycles of 250 mg once in a day for 5 days) patient pro-gressed with disease as seen by worsening of symptoms and increase in the size of tumour. The probable reason for lack of effectiveness to TMZ could be the presence of high MGMT activity [10].…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al reported that Nimotuzumab is effective in improving the response rate or the survival time when it is used with or without radiotherapy; chemotherapy in high-grade glioma [10]. Westphal et al in a phase III study also assessed the efficacy of Nimotuzumab using a higher doses and found progression free survival rate (PFS) and overall survival (OS) at 12 months higher in a group of subjects treated for 12 consecutive a weekly infusions of 400 mg of nimotuzumab during standard radiotherapy along with temozolomide followed by biweekly infusions of 400 mg (PFS = 25.5%, OS = 679 days) than the group of subjects treated with standard radio and chemotherapy alone (PFS = 20.3%, OS = 596 days).…”
Section: Discussionmentioning
confidence: 99%